Inhibitory Effects of Tricyclic Antidepressants on Human Liver Microsomal Morphine Glucuronidation: Application of IVIVE to Predict Potential Drug-Drug Interactions in Humans - Uchaipichat, Verawan (Current Drug Metabolism, 2023)
Background: Tricyclic antidepressants (TCAs) are commonly co-administered with morphine as an adjuvant analgesic. Nevertheless, there remains a lack of information concerning metabolic drug-drug interactions (DDIs) resulting from TCA inhibition on morphine glucuronidation. Objective: This study aimed to (i) examine the inhibitory effects of TCAs (viz., amitriptyline, clomipramine, imipramine, and nortriptyline) on human liver microsomal morphine 3- and 6-glucuronidation and (ii) evaluate the potential of DDI in humans by employing in vitro-in vivo extrapolation (IVIVE) approaches. Method: The inhibition parameters for TCA inhibition on morphine glucuronidation were derived from the in vitro system containing 2% BSA. The Ki values were employed to predict the DDI magnitude in vivo by using static and dynamic mechanistic PBPK approaches Results: TCAs moderately inhibited human liver microsomal morphine glucuronidation, with clomipramine exhibiting the most potent inhibition potency. Amitriptyline, clomipramine, imipramine, and nortriptyline competitively inhibited morphine 3- and 6-glucuronide formation with the respective Ki values of 91 ± 7.5 and 82 ± 11 μM, 23 ± 1.3 and 14 ± 0.7 μM, 103 ± 5 and 90 ± 7 μM, and 115 ± 5 and 110 ± 3 μM. Employing the static mechanistic IVIVE, a prediction showed an estimated 20% elevation in the morphine AUC when co-administered with either clomipramine or imipramine, whereas the predicted increase was <5% for amitriptyline or nortriptyline. PBPK modelling predicted an increase of less than 10% in the morphine AUC due to the inhibition of clomipramine and imipramine in both virtual healthy and cirrhotic populations. Conclusion: The results suggest that the likelihood of potential clinical DDIs arising from tricyclic antidepressant inhibition on morphine glucuronidation is low.
Keywords: tricyclic antidepressants